DEJECTION AND REJECTION OF TRUST IN SUZAN LORI PARK’S VENUS - J. CHITRAand; K. SUMATHI (International Journal of Psychosocial Rehabilitation, 2020)
This paper critically explores various problems faced by the American women in the western societies. Parks characters also undergo a variety of experiences, often Painful under the patriarchal oppression in the society portrayed by Suzan Lori Parks in her play, Venus. Parks has excellently provided a vivid picture of the treachery encountered by the black people in America such as dehumanization, historical sexualization of black female bodies, criminality duplicity, fraudulance, Female subordination, racism and betrayal of trust. These have all been the outcome of colonial violence. Park has also cautioned the world to be aware of such horrors and put an end to offences like sexual exploitation, killings, corruption of mind and betrayal of trust. The paper traces the history of Venus and the social victimization against the African women. It also talks about the freedom of African women to express their identity in the society. Finally the paper reveals a clear picture of victims of battering, Murder, ridicule, molestation and assault. Parks has exposed such flaring injustice done to women by men. Venus tries to make her life better but she is pulled down by the Male dominated western society. Finally the paper points out the lusty eyes that considers women as a mere sexual object in the west.